Plan de negocio para la producción y comercialización de bebida elaborada con base de horchata - Tamayo Vaca, Tito Livio (2016)
In Ecuador there are regulations and special tariffs for artificial, energy and sugary drinks, because of the damage they cause on health of people. Similarly, there is a tendency in Ecuadorian society in general, to take care of their health and the practice of sports and these people tend to seek natural drinks which could give them benefits according to their needs. In addition, daily activities generate exhaustion in people who look to consume products that provide them additional energy and hydration. Thus was born the concept of Hortea, a natural drink with horchata flavor, made with a mixture of different ancestral natural herbs produced in the province of Loja, in southern Ecuador. This product has been designed for men and women between 20 and 50 years Quito, who take care of their health and have daily activities that produce exhaustion and stress in their lifes. Precisely because of exhaustion, Hortea has an added value, ginseng, which is an ancient native Korean root that provides natural energy to whoever consumes it. The overall marketing strategy is differentiation focused on the marketing target, it provides more than one benefit in just one product. The investment project has a value of $ 98,196.43 in which 60% is financed by own capital and 40% is financed by a loan with a repayment term of 5 years. To identify the financial profitability of the project, a NPV of $ 101.783,22 was obtained and an IRR of 36.31%